Ks. Stanisław Łach, Księga Wyjścia: wstęp, przekład z oryginału, komentarz (Pismo święte Starego Testamentu KUL 1,2; Poznań: Pallottinum 1964) - Zawiszewski, Edward (The Biblical Annals, 2017)
Book review